Deciphering the genetic basis of novel traits that discriminate useful and non‐useful biomass to enhance harvest index in wheat - Dipendra Shahi; Jia Guo; Md Ali Babar; Sumit Pradhan; Muhsin Avci; Naeem Khan; Jordan McBreen; Smita Rayamajhi; Zhao Liu; Guihua Bai; Paul St. Amand; Amy Bernardo; et al. (The Plant Genome)
Abstract Wheat (Triticum aestivum L.) production must be doubled in the next 25 years to meet the global food demand. Harvest index (HI) is an important indicator of efficient partitioning of photosynthetic assimilates to grains. Reducing competition from alternative sinks, such as stems, and deviating assimilates toward grain increase grain number (GN), HI, and grain yield (GY). Novel partitioning traits have great potential to be utilized in wheat breeding programs to increase HI. In this study, we evaluated 236 US facultative soft wheat genotypes for multiple stem and spike partitioning traits at 7 days after anthesis, and for GN, HI, and GY in two locations of Florida in 2016–2017 and 2017–2018 wheat growing seasons. The panel was genotyped with 20,706 single nucleotide polymorphisms generated by genotype‐by‐sequencing approach. Spike partitioning index (SPI) showed negative significant correlations with lamina partitioning index and true stem partitioning index. Internode 2 and 3 lengths and partitioning indices had significant negative correlations with SPI and HI. The results indicate enhanced competition for assimilates between spikes and second and third internodes during stem elongation. Genome‐wide association study (GWAS) identified 114 unique significant marker‐trait associations (MTAs) for 12 traits, and 58 MTAs were found within genes that encode different proteins related to biotic/abiotic stress tolerance and other functions. Significant MTAs identified in the GWAS were converted into kompetitive allele specific PCR markers. Some of the markers were validated and can be effectively employed in marker‐assisted selection to improve HI, GY, and GN.